New challenges in central banking: Monetary policy governance and macroprudential issues - Ernest Gnan; Donato Masciandaro (SUERF - The European Money and Finance Forum, 2017)
Which are the new frontiers in central banking? Which things have changed in the aftermath of the financial, economic and sovereign debt crisis? These are questions raised frequently by central bankers, academics and interested observers alike. There are quite a few areas to cover in answering these questions. The aim of the workshop organized jointly between SUERF and the Baffi Carefin Centre of Bocconi University in Milan on 8 June 2017 was to focus on two areas: monetary policy committees, on the one hand, and new prudential responsibilities, on the other hand. This chapter summarizes the findings from the workshop. Not all papers are included in this volume.
Keywords: D02; D71; D78; D91; E47; E52; E58; E65; F37; G28; 330; Monetary policy; central bank committees; gender diversity; macroprudential policy; bank regulation; sovereign debt crisis; European Economic and Monetary Union